2022
DOI: 10.4258/hir.2022.28.4.376
|View full text |Cite
|
Sign up to set email alerts
|

Simulation Education Incorporating Academic Electronic Medical Records for Undergraduate Nursing Students: A Pilot Study

Abstract: Objectives: Academic electronic medical records (AEMRs) can be utilized for a variety of educational programs that can enhance nursing students’ nursing informatics and clinical reasoning competencies. This study aimed to identify the applicability and effectiveness of simulation education incorporating AEMRs.Methods: We developed simulation education scenarios incorporating AEMRs and evaluated them with 76 third- and fourth-year nursing students from five nursing schools using a mixed-methods design. We incor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…At the undergraduate level, the main focus of education delivered was on telehealth and/or telenursing [30][31][32][33][34][35][36][37][38][39][40] and developing competency in using the EHR through the simulated EHRs [71][72][73][74][75][76][77][78][79][80]. Two studies focused on NI education [83,84].…”
Section: Digital Health and Ni Educational Interventions At The Under...mentioning
confidence: 99%
See 3 more Smart Citations
“…At the undergraduate level, the main focus of education delivered was on telehealth and/or telenursing [30][31][32][33][34][35][36][37][38][39][40] and developing competency in using the EHR through the simulated EHRs [71][72][73][74][75][76][77][78][79][80]. Two studies focused on NI education [83,84].…”
Section: Digital Health and Ni Educational Interventions At The Under...mentioning
confidence: 99%
“…Integration was mostly as a stand-alone intervention, a few studies reported integration as part of the first year nursing clinical course [71], a clinical course [74], or as part of a fundamentals of nursing course [79]. A key aspect of using the simulated EHRs focused on developing documentation skills [71][72][73]77,80]. Case scenarios were used in most interventions, some included an additional didactic content [71] or provided orientation through videos, webinars and opportunities to practice [72,73,79,80].…”
Section: Interventions Focused On Ehr Educationmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, due to the busy and complex clinical environment, observation-based practice still makes it difficult for nurses to teach EMR to nursing students [9]. This means that EMR education takes into account the learner's situation, and students cannot practice EMR operation sufficiently, resulting in decreased satisfaction with the practice [5,10].…”
mentioning
confidence: 99%